Chemistry of brine in an unconventional shale dominated source bed understanding water- organic material-mineral interactions during hydrocarbon generation - Alvarez, Helder Ivan (Kansas State University, 2015)
The exploration and development of unconventional shale plays provide an opportunity to study the hydrocarbon generation process. These unconventional plays allow one to investigate the interactions between the fluid, mineral, and organic material that occur in a hydrocarbon-generating source bed, before any changes in composition that may occur during secondary migration or post migration processes. Previous studies have determined the chemical constituents of formation waters collected from conventional reservoirs after secondary migration has occurred. This investigation targets formation waters collected from the Woodford shale that acts as both source and reservoir, therefore samples have yet to experience any changes in composition that occur during secondary migration. This investigation focuses on the major element and trace element chemistry of the formation water (Cl, Br, Na, K, Rb, Mg, Ca, Sr, and Rare Earth Elements), which has been compared to chemical constituents of the associated crude oil and kerogens. Analytical data for this investigation were determined by the following methods; Ion Chromatography, Inductively Coupled Plasma Mass Spectrometry (ICP-MS), and Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES). The information is used to assess the presence of different sources of water that constitute the formation water, and also to investigate interaction between different minerals and formation waters within the source beds. The formation water data also yields new insights into compartmentalization of oil-gas rich zones within the source beds.
Keywords: Petroleum geology; Formation water; Rare earth elements; Woodford shaleGeology; Geochemistry (0996)